If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14+x=3(3x+2)
We move all terms to the left:
14+x-(3(3x+2))=0
We calculate terms in parentheses: -(3(3x+2)), so:We get rid of parentheses
3(3x+2)
We multiply parentheses
9x+6
Back to the equation:
-(9x+6)
x-9x-6+14=0
We add all the numbers together, and all the variables
-8x+8=0
We move all terms containing x to the left, all other terms to the right
-8x=-8
x=-8/-8
x=1
| ^2+12x=-25 | | y-8/2=9 | | -6+2m=-3(3m+2) | | 7z−4=52 | | 9(5y=36) | | 16x-14=9x-7 | | 5x-3(1-7x)=205 | | 3(x+4)+2=6x-3(-4+x) | | 5t-5=9t+5 | | -4(-5r+2)+1=-107 | | (6x+3)+(7x-19)=180 | | 7(5+7x)-4=-263 | | -2(5p+8)=-86 | | 6x-3(x+7)=x+51 | | 5x-2=3×-8 | | 1/2m-3/4=16 | | 5x+6=2x+4x | | 5(2n+1)=8(5n+1)+5 | | x+4(–3x+4)=–6 | | 15x(2+4)=34 | | n/0.5=0.02/5 | | 5x-10=92x+40 | | 3/7x-2/5-11/35=x | | -3(x+9)=2x-22 | | 4w+5-w=2(w-3) | | 15x(2+4)=90 | | 4=-7v+5(v+4) | | x-2/3-3-2x/6=x+5/4-29-5x/12 | | -26=8u+6(u-2) | | 4x+25=25 | | 41=2x41 | | 0.75f+3=5 |